Assessing the structure of UK environmental concern and its association with pro-environmental behaviour. (September 2015) - Rhead, Rebecca; Elliot, Mark; Upham, Paul
Abstract: Understanding the structure and composition of environmental concern is crucial to the study of society's engagement with environmental problems. Here, we aim to determine if components of the VBN model emerge when applying a combination of exploratory and confirmatory factor analysis to a large UK dataset, one designed without a priori commitment to a theoretical model. A three-factor model was confirmed to be the most substantively and methodologically optimal. Two of the factors correspond to the VBN's ecocentric and anthropocentric factors. However, the third factor does not routinely map onto the third factor of the VBN (ecocentric concern). We have called our factor 'denial', as high scorers tend to be responding positively to statements that would suggest inaction. The association between these factors and level of reported pro-environmental behaviour is assessed. Highlights: Environmental concern studied on representative UK data. New denial component of environmental concern found. Concern for nature (not humanity) is significant predictor of reported behaviour.